THE STUDY OF SOCIO-ECONOMIC EFFECTS OF ADOPTING DIGITAL BANKING SERVICES IN NAGPUR DISTRICT - Wankhede, Yogesh Subhashrao; Kanetkar, Medha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rapid adoption of digital banking services has transformed financial transactions, influencing the socio-economic conditions of users. This study examines the impact of digital banking adoption on financial inclusion, convenience, economic empowerment, and overall financial behavior in Nagpur District. By analyzing customer experiences, transaction patterns, and financial accessibility, the research highlights the role of digital banking in enhancing financial literacy, reducing cash dependency, and improving economic stability. The findings suggest that digital banking positively contributes to socio-economic development, bridging the financial gap and fostering a more inclusive banking system.